2013
DOI: 10.1161/strokeaha.112.675231
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Therapy in Experimental Intracerebral Hemorrhage Associated With Rivaroxaban

Abstract: T hromboembolism in atrial fibrillation is a major cause of stroke.1 Oral anticoagulation (OAC) with the vitamin K antagonist warfarin or one of the new direct oral anticoagulants (nOAC) is highly effective for stroke prevention in atrial fibrillation. [2][3][4][5] The most severe complication of long-term anticoagulation is intracranial hemorrhage. Indeed, intracerebral hemorrhage (ICH) during therapy with vitamin K antagonist is responsible for 88% of all hemorrhage-associated deaths caused by anticoagulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 35 publications
6
81
0
2
Order By: Relevance
“…32,33 Using the Neoplastin prothrombin time assay that is sensitive to rivaroxaban, 34 30 mg/kg rivaroxaban prolong the prothrombin time two-to threefold for at least 4 hours. 17 In the present study, rivaroxaban reduced the activity of coagulation factors II and X ( Figure 1A). Elevated values of rivaroxaban concentration and anti-factor Xa activity remain detectable even 24 hours after rivaroxaban application ( Figures 1E and 1F).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…32,33 Using the Neoplastin prothrombin time assay that is sensitive to rivaroxaban, 34 30 mg/kg rivaroxaban prolong the prothrombin time two-to threefold for at least 4 hours. 17 In the present study, rivaroxaban reduced the activity of coagulation factors II and X ( Figure 1A). Elevated values of rivaroxaban concentration and anti-factor Xa activity remain detectable even 24 hours after rivaroxaban application ( Figures 1E and 1F).…”
Section: Discussionsupporting
confidence: 58%
“…4,6 Although present and previous data justify withholding thrombolytic treatment in patients with warfarin in the therapeutic INR range, our findings may suggest that hemorrhagic adverse events do not occur more frequently in patients anticoagulated with rivaroxaban than in nonanticoagulated stroke patients. Interestingly, high doses of rivaroxaban 17 and dabigatran 42 are necessary to increase intracerebral hemorrhage volume in murine intracerebral hemorrhage that is induced by striatal collagenase injection. In contrast, the same high dose (30 mg/kg) of rivaroxaban did not cause excess secondary hemorrhagic transformation after thrombolysis in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…6 Data on NOAC-associated ICH (NOAC-ICH) outside randomized trials are limited, and there is widespread concern that, without any currently available specific antidotes, those who have ICH while on NOACs might have larger ICH volumes and worse clinical outcomes than patients with warfarin-associated ICH (warfarin-ICH). 7,8 Although experimental models show that dabigatran 9 and rivaroxaban 10 -unlike warfarindo not increase ICH volume unless given at supratherapeutic doses, few data are available on the clinical and radiologic characteristics of NOAC-ICH. A small study from Japan recently reported that in 5 patients with ICH associated with the NOAC rivaroxaban, the mean hematoma volume was smaller than in a comparison group of ICH associated with warfarin, 11 and that functional outcomes were better in the NOAC group.…”
mentioning
confidence: 99%
“…PCCs are the preferred nonspecific hemostatic agent for NOAC reversal; they are plasma-derived products that contain three (factors II, IX, and X) or four (factors II, IX, X, and VII) clotting factors, in addition to variable amounts of heparin and the natural coagulation inhibitors protein C and protein S. Animal studies have demonstrated that PPCs have a variable ability to normalize anticoagulation parameters and to prevent or attenuate bleeding seen with NOAC usage. 14,[19][20][21][22][23][24][25] The limited data available in humans are restricted to healthy volunteers only. In three small, randomized, placebo-controlled studies involving between 12 and 93 patients, PCC use reversed the anticoagulant effects of rivaroxaban and edoxaban, but not of dabigatran.…”
Section: General Supportive Measuresmentioning
confidence: 99%